STRATEGI PEMBELAJARAN BAHASA ARAB AKTIF (KEMAHIRAN ISTIMA’ DAN TAKALLUM) - M. Khalilullah (Sosial Budaya, 2011)
Strategy is one of important thing in teaching a language, moreover in teaching Arabic. The suitable strategy in teaching Arabic is based on the material and the condition of the students. Enjoyable or not the process of teaching and learning Arabic would determine the result expected of the teaching itself. If the beginning of the process of teaching and learning has already implemented active and joyful strategy, the students will be interested in the process of learning Arabic. Arabic active learning is focusing on creating various conditions in which it enables the students to utilize their time to study. The teacher in the concept of active learning will no longer as the main source who transfers knowledge to the students. Active learners place the teacher as a facilitator who creates conducive class to make the process of teaching and learning be better. In learning a language, the first skill that the students have is listening (istimak). The ability in listening means that the students are able to comprehend Arabic utterances correctly and well. After mastering this skill, there is a process again called takallum (speaking). Speaking ability in general is about two sides; the speaker and the listener.